Ascogregarina (Apicomplexa: Lecudinidae): An overview of its distribution and pathogenicity on Aedes aegypti and Ae. albopictus development - Thiago Nunes Pereira; Josiane Somariva Prophiro; Guilherme Liberato da Silva; Joice Guilherme de Oliveira; Onilda Santos da Silva (Biotemas)
Ascogregarina species are protozoa that belong to the phylum Apicomplexa and parasitize several species of invertebrates, including some important mosquito species involved in transmitting arboviruses, such as dengue, yellow fever, chikungunya and Zika virus. The most frequent gregarine species reported for mosquitoes are Ascogregarina culicis, A. taiwanensis and A. barreti, which have Aedes aegypti, Ae. albopictus and Ae. triseriatus as natural hosts, respectively. Studies have shown that parasitism by some Ascogregarina species can negatively influence the biological development of mosquitoes and that this influence depends on their environmental distribution. In this review, we revise the distribution of Ascogregarina species in several countries and discuss how these parasites influence the development of mosquitoes and could possibly be used as a mosquito control.